Development of micronutrients rich homemade extruded food products with the incorporation of processed foxtail millet, wheat and chickpea - Gautam, L; Chaturvedi, N; Gupta, A (Indian Journal of Community Health, 2014)
Background: Food based approaches are recognized as an essential part of an urgently needed more comprehensive strategy for improving nutrition by increasing the availability and consumption to combat iron and other micronutrient deficiencies. Aims & Objective: The specific objective of the study was utilization of Foxtail millet (Setariaitalica) along with other flour for production of micronutrients rich ready-to-eat snack products using homemade extrusion cooking. Material and methods: Methods Composite flour were prepared using processed Foxtail millet flour (FMF) and other processed flours namely; wheat flour (WF), and chick pea flour (CPF). Nutritional properties of the blends were analyzed by using standard procedure. Two homemade extruded products namely; namkeensev, seviyan were prepared with four treatments T0, T1, T2, & T3. The commonly consumed recipes were developed by incorporating 50%, 75% and 100% of best result malted composite flour (FMF+CPF+WF). Results: The organoleptic qualities of these extruded samples were analyzed by panelists on a 9 point hedonic scale. The result indicate that the processed composite flour (FMF+CPF+WF) based products were significantly accepted at the level of p<0.05 50% incorporation followed by 75% and 100% respectively. Conclusions: The present study conclude that, processed composite flour (Foxtail millet; wheat; chickpea) in the ratios of (50:50) could be used to produce nutritive quality of homemade extrudates with acceptable sensory properties as they deliver vehicles for malnourished children.